Can educational video games increase high school students' interest in theatre?. (September 2015) - Manero, Borja; Torrente, Javier; Serrano, Ángel; Martínez-Ortiz, Iván; Fernández-Manjón, Baltasar
Abstract: The value of educational video games in education is undeniable and the benefits of using video games in classroom instruction have been proved by many researchers. Nevertheless, these benefits have not been proved sufficiently for some domains, such as artistic disciplines. In this paper we explore the effects of an educational video game on high school students' interest towards classical theatre. The game covers the story of "The Foolish Lady" ( La Dama Boba ) based on the homonymous classic theatre play by Spanish playwright Lope de Vega. A mixed experimental design was followed, whereby researchers conducted pre-tests and post-tests to estimate the effect of playing the video game on student interest (within-subjects factor) towards theatre. We also measured changes in linguistic knowledge and knowledge about the play. The experiment was carried out with 754 students from 8 different schools in the Madrid region in Spain, divided into experimental group and two control groups. With the objective of improving the comparative power of the study, two control groups were used: (1) traditional teaching with the usual teacher and, (2) as the best educative case we could implement, teaching with a professional actor who had played the male protagonist of the theatre play. The experimental group played the video game. Results show that the video game was more effective in incrementing students' interest in theatre than the traditional class, but slightly less effective than the class with the actor. On the other hand, game and teacher approaches obtained similar results in the improvement of students' knowledge about the play's plot and some linguistic concepts. These results open up a new horizon in using video games as motivators in different artistic domains. Highlights: An educational video game created to enhance high schoolers' interest on theatre. We compare the game versus a lecture by (1) the regular teacher or (2) an actor. 757 students split in 3 groups participated in a pre-post experiment. The game increases interest, play and linguistic knowledge among the students. Video games can be used as motivators towards theatre.